Challenges and perspectives of Chagas disease: a review - Marques Pereira, Paulo Camara [UNESP]; Navarro, Elaine Cristina [UNESP] (Biomed Central Ltd., 2013)
Chagas disease (CD), also known as American trypanosomiasis, is caused by the flagellated protozoan Trypanosoma cruzi, and affects an estimated 8 to 10 million people worldwide. In Latin America, 25 million people live in risk areas, while in 2008 alone, 10,000 CD-related deaths were reported. This review aimed to evaluate the challenges of CD control, future perspectives, and actions performed worldwide to control expansion of the disease and its impact on public health in Latin America.
Keywords: Control of Chagas disease; Epidemiology; Transmission